Case of thrombosis of the portal vein and its branches in a patient seropositive for Borrelia antigens - E V Reznik; M P Prushkovskaya; E D Presnova; N A Novikova; R A Ivaschenko; E I Dedov; A E Nikitin; I G Nikitin (Терапевтический архив, 2018)
Borreliosis after sucking ticks is an acute problem in the world. People do not go to doctors after that often, which leads to the development of various complications. Thrombosis of veins of various localization can be one of them. Thrombosis of the portal vein represents a significant problem too with high morbidity and mortality. The risk factors for splanchnic vein thrombosis include infections, but its relationship with borreliosis has not been studied. А 34-year-old man with chronic helicobacter-associated gastritis and gallstones was hospitalized due to development during the last 11 days of epigastric pain and fever to 38.7 °C after a picnic at the forest without a registered tick bite. The blood leukocytes were increased to 11.2*109/l, lymphocytes 70%, C-reactive protein 34.6 mg/l, procalcitonin 0.195 ng/ml. The multispiral computed tomography of the abdominal cavity revealed thrombosis of portal, lienalis and superior mesenteric veins. D-dimer was 1.98 mcg/ml, antithrombin III 75%. JACK2V617F, oncological, rheumatic, thrombophilia markers, blood and urine cultures were negative. A high concentration of anti-Borrelia burgdorferi IgM 62.2 U/ml and its increasing to 190 U/ml in dynamics was revealed at the immunofluorescence assay. Anti-Borrelia IgM to OspA, p31 and OspC, p25 were detected at the immunoblotting assay. Anticoagulation, doxycycline, detoxification therapy reduced pain and normalized temperature and inflammation markers. Vein thrombosis was not detected at the control tomography after 2 weeks. Despite that the combination of thrombosis and borreliosis is rare, it is necessary to screen for Borrelia antigens in patients with splanchnic vein thrombosis and fever.